2021
DOI: 10.21203/rs.3.rs-148923/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender-Specific Associations of Speech-Frequency Hearing Loss, High-Frequency Hearing Loss, and Cognitive Impairment Among Older Community Dwellers in China

Abstract: Objectives The purpose of this study was to investigate the relationship between speech-frequency hearing loss (SFHL), high-frequency hearing loss (HFHL), and cognitive impairment (CI). Then to determine whether there are any differences in gender among older community dwellers in China. Methods This study involved 1,012 adults aged ≥ 60 years (428 male; average age, 72.61 ± 5.51 years). The participants had their hearing and cognition measured using pure tone audiometry and Mini Mental State Examination (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…We found that limitations in daily behavioral ability had a significant effect on cognitive function. This finding is similar to the results of previous studies (Wang et al, 2021; Wu et al, 2021). Decreased ADL ability is a risk factor for cognitive function and frailty, indicating that physical and mental activities are interrelated (Wu et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…We found that limitations in daily behavioral ability had a significant effect on cognitive function. This finding is similar to the results of previous studies (Wang et al, 2021; Wu et al, 2021). Decreased ADL ability is a risk factor for cognitive function and frailty, indicating that physical and mental activities are interrelated (Wu et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Table 1 summarizes the 35 included studies, among which three studies were divided into two substudies each, by gender or cognitive impairment/dementia ( Pan et al, 2021a ; Wang et al, 2020a , 2021a ). Fourteen studies used validated audiology methods to measure hearing, including pure-tone audiometry and speech reception thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…The type of hearing loss (HL) most commonly encountered in older adults is ARHL [8], and its clinical manifestation is speech perception difficulty in a noisy environment. Speech perception is a process in which people hear, interpret, and understand the sounds of language [9]. Instinctively, cognitive functions are involved in speech perception, but few studies have investigated their link.…”
Section: Introductionmentioning
confidence: 99%